THE HISTORY OF MURAL PAINTINGS IN LAO PDR BETWEEN 2322-2436 BE - Surin Sresangngam; Advisor: Asst. Prof. Burin Plengdeesakul?; Co-Advisor: Asst. Prof. Dr. Preechawut Apirating (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The aim of this research article was to study the history and the development of the mural paintings in Lao PDR during the year 2322-2436 BE through the qualitative research process. The study was done on the mural paintings in Lao PDR that exist in Vientiane and Luang Prabang city. The tools used for this research were surveys, observation, interviews, and group discussions. The data was analyzed under theory and presented with descriptive analysis. The research results show that the mural paintings in Lao PDR during 2322-2436 BE were created during the Lan Xang kingdom, which was under the suzerainty of Siam at the time. The paintings consist of 1) mural paintings in Sisaket temple, Vientiane 2) mural paintings in Long Khoun temple, Luang Prabang 3) mural paintings in Hat Siao Temple, Luang Prabang 4) Siphoutthabat Temple, Luang Prabang and 5) Pa Huak Temple, Luang Prabang. The oldest mural paintings are the paintings inside the sim of Sisaket temple, Vientiane, in which King Anouvong ordered the paintings to be painted during the restoration of the temple during 2366-2367 BE. Later, the paintings also appeared in Luang Prabang in Long Khoun Temple, Hat Siao Temple, and Siphoutthabat Temple, which were painted during the time of Chao Chantharath in the year 2396 BE. That last set of paintings are the paintings in Pa Huak Temple in Luang Prabang painted by Phraya Si Maha Nam during the time of Chao Chantharath in the year 2404 BE. Mural paintings from Lan Xang kingdom were influenced by the mural paintings of the Rattanakosin era of Siam. In the beginning, the paintings were adjusted to the Lan Xang culture by painting the story of Kalaked, which was popular in Lan Xang kingdom during the time. The paintings were, later, adjusted to be about the way of life and the culture of Lan Xang, which reflects the identity of the mural paintings of the Lan Xang Kingdom, Lao PDR.